Prototype Design Monitoring System of A Salt Tunnel Processing Using Heater Based on Smartphone Application - Eka Dina; Umi Fadlilah (Evolution of Information, Communication and Computing System, 2025)
Indonesia is an archipelago that has a vast ocean with the second-longest coastline in the world. This considerable marine potential affects the variety of livelihoods of people in Indonesia, especially in coastal communities. One of the many livelihoods of coastal communities is being a salt farmer. These farmers still utilize the sun's heat for the evaporation process, so salt production depends on weather factors.  If the weather is rainy or cloudy, then the production will run very long or even stop which causes the production yield to decrease. With this condition, it is necessary to have a technology that can help the process of evaporating seawater during cloudy/rainy weather conditions, and even at night farmers can still carry out the process of making salt with a remote monitoring system. Researchers will design and build a prototype for monitoring tunnel salt processing by utilizing a heater for alternative seawater evaporation processes. This requires regular monitoring of the temperature in the tunnel, so a DS18B20 temperature sensor is used. In addition to the temperature sensor, it is also necessary to monitor the weather around the tunnel with an FC-37 rain sensor. Monitoring of the salt water concentration is done using a water pH sensor. The readings from all sensors will be displayed on the I2C 1602 LCD (Liquid Crystal Display) screen. This prototype will be applied directly to a mini tunnel mockup that uses UV plastic material for testing. All monitoring is expected to be done in real-time and flexibly from anywhere. The heater that will be applied should also be able to be controlled remotely. Therefore, researchers hope that with the use of an application-based monitoring system to monitor and control the evaporation process in salt the resulting production is maximized and effective.